Different approaches to technology transfer by government and academy - Porath, Amiram (2015)
The paper will present the conflict between the natural preference of technology transfer organisations (TTO) regarding commercialisation for the licensing option and the government preference for spin–offs. The difference in preferences is based on the impact both alternatives have on measurable employment rate increase. It will further suggest that the government preference expressed in both funding and availability of support tools, aimed to support the preferred government alternative, is showing reduced results than expected, due to the conflict. The paper suggests a methodology for governments to develop support tools that would enhance the chances of economic development based on the work of the research organisations. The paper further describes the requirements from the business environment, and the complementary nature of successful tools to be developed. Further empirical research is recommended based on the methodology.